2021
DOI: 10.1155/2021/3010577
|View full text |Cite
|
Sign up to set email alerts
|

MED1 Deficiency in Macrophages Accelerates Intimal Hyperplasia via ROS Generation and Inflammation

Abstract: Mediator complex subunit 1 (MED1) is a component of the mediator complex and functions as a coactivator involved in the regulated transcription of nearly all RNA polymerase II-dependent genes. Previously, we showed that MED1 in macrophages has a protective effect on atherosclerosis; however, the effect of MED1 on intimal hyperplasia and mechanisms regulating proinflammatory cytokine production after macrophage MED1 deletion are still unknown. In this study, we report that MED1 macrophage-specific knockout (MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Therefore, we assessed the effect of myricanol on intimal hyperplasia after carotid artery wire ligation and found that 14-day' treatment of myricanol can significantly diminish the intimal hyperplasia. In addition, inflammatory cytokines produced by activated macrophages are the direct promoters of neointimal formation (Zhang et al, 2021). And our results showed that myricanol can also inhibit the macrophage infiltration after carotid artery wire ligation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, we assessed the effect of myricanol on intimal hyperplasia after carotid artery wire ligation and found that 14-day' treatment of myricanol can significantly diminish the intimal hyperplasia. In addition, inflammatory cytokines produced by activated macrophages are the direct promoters of neointimal formation (Zhang et al, 2021). And our results showed that myricanol can also inhibit the macrophage infiltration after carotid artery wire ligation.…”
Section: Discussionsupporting
confidence: 52%
“…Immunofluorescence staining showed that the myricanol-treated ligation surgery group had significantly inhibited Ki67 expression (Supplementary Figures 5A,B). In addition, macrophages are known to play a role in the progression of intimal hyperplasia and other cardiovascular disorders (Zhang et al, 2021). Our results exhibited that the expression of F4/80 significantly increased in the ligation surgery group comparing with the sham surgery group, While the myricanol treatement significantly decreased F4/80 expression (Supplementary Figures 5C,D).…”
Section: Myricanol Inhibits the Neointimal Hyperplasia Induced By Car...mentioning
confidence: 53%
“…Activated ARNT2 in this study might be a therapeutic target to facilitate AVF maturation, as aryl hydrocarbons have been suggested as a therapeutic target in cardiovascular diseases [ 28 , 29 ]. Excessive intimal hyperplasia is also a result of increased ROS production and inflammation, mediated by macrophages that are deficient in MED1 [ 30 ]. Inhibited MED1 ( Table 6 ) and the infiltration of pro-inflammatory immune cells, including macrophages, in the thrombosed and intimal hyperplasia region of femoral arteries in this study support the notion of the presence of inflammation [ 12 ] and a the possible role of MED1-deficient macrophages in early thrombosis and AVF failure.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular Intimal hyperplasia (VIH) is a process in which the vascular intima becomes thickened due to the appearance of unexpected cells and proteoglycan-rich extracellular matrix between the internal elastic lamina of the vessels and vascular endothelia ( 3 ). It has been found that VIH increases lipoprotein retention in the vascular intima and accelerated atherosclerosis, and thus becomes an initial pathological process for AS development ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…VIH contains cell types including macrophages that could transform into foam cells, which are critical for plaque formation ( 7 ). It is known that plaque macrophages are heterogeneous ( 4 ). Recently, it was shown that CD11c+ macrophages appeared to be more involved in active plaque progression ( 8 ).…”
Section: Introductionmentioning
confidence: 99%